The impact of the Covid-19 pandemic on dental education – literature review (Research, Society and Development, 2022)
The suspension of clinical and laboratory classes due to the Covid-19 pandemic had an impact on Dental Education, especially for students, causing learning problems and impacting their quality of life. Thus, the present study aims to verify the impact of dental education during the Covid-19 pandemic. For this, a survey of publications was carried out in three databases: 1. CAPES Journal Portal; 2. Scielo and 3. Lilacs. The research involved the following combinations of keywords: (a) Dental students “and” Covid-19 pandemic; (b) Covid-19 “and” dental education. From definitions, criteria and key word combinations 96 publications were identified for the study. The final sample consisted of 10 articles. The results showed a negative predominance of the pandemic both in the emotional aspect and in relation to the teaching and learning of dentistry students. This allows us to conclude that actions need to be taken adopted so that, if by chance, future episodes happen, the educational system can determine previous measures so that the consequences are mitigated. The need to reinvent itself in these periods is essential, especially because it is something that can have an indeterminate impact and, it will surely transform the concept of teaching.